Efficient Design of Reinforced Columns: Insights into Lateral Confinement and Performance - Singha, Badhon; Chowdhury, Nafis Niaz; Sakib, Mohammad Atiqur Rahman (International Journal of Applied Sciences and Smart Technologies, 2025)
In structural engineering and architecture, a column is a vertical load-bearing member crucial for supporting compressive loads. Reinforced concrete columns consist of both confined and unconfined concrete. Pioneering experiments by Mander et al. (1988a) (Observed stress–strain behavior of confined concrete, 1988a) and (1988b) (Theoretical stress-strain model of confined concrete., 1988b) scrutinized the performance of columns under seismic strain rates, revealing that optimal performance is achieved through meticulous identification of maximum stress and strain locations. The initial stage is to realize the specified attributes derived from SAAP200, which are then included into the ABAQUS finite model simulation. A Validation was conducted by finite model simulation process in Abaqus by comparing results with those presented by Guadagnuolo et al. (2020) to assess the accuracy and reliability of the methodology. The resulting Load vs Displacement relations are then subjected to validation based on property-centric criteria. The efficacy of outcomes is highlighted by presenting distinct load vs displacement curves for concrete columns at various pitch distances. Excessive spacing between hoops can result in early spalling and reduced strength, whereas an increased hoop area in the intermediate zone improves both load-carrying and deformation capabilities.